(untitled) (Research, Society and Development, 2022)
Cleft lip and palate (CLP) is characterized by anatomical changes of the nose, upper lip and palate, being the most prevalent craniofacial anomaly in the human population. Feeding a cleft patient is usually a matter of concern for parents, as nutrition is linked to the child’s survival. This work intends to describe the process of elaborating a manual for the introduction of complementary feeding in patients with cleft lip and palate. The feeding of the patient with cleft lip and palate has a food composition very similar to that of an infant without this alteration, however, due to the high occurrence of nasal leaks and choking reported by the parents, it is important that the child remains in a semi-sitting position during feeding. The way of introducing complementary feeding in patients with cleft lip and palate is not yet fully elucidated in studies, therefore, the elaboration of a booklet is extremely important for the guidance of parents, caregivers and professionals in this area. It is hoped that this instrument will be easy to understand for the patients’ families and that it will guide professionals in the area of cleft lip and palate, and that soon, the validation of this booklet will be carried out by professionals specializing in the subject.